Sodobna farmacevtska biologija - Lunder, Mojca (Farmacevtski vestnik, 2020)
Pharmaceutical biology covers a broad field of pharmaceutical sciences, focusing on development, assessment, and production of biological drugs. It combines fundamental research, such as deciphering cellular or molecular pathways perturbed in disease and consequent new drug target identification/ validation, with applied science, i.e., development of innovative therapeutic approaches for untapped diseases, discovery of new biological drugs and identification of disease markers for improved diagnosis. Here, we briefly review the fields of pharmacognosy, cell and molecular biology (with relevance to pharmaceutical biology), recombinant biotherapeutics, synthetic peptide drugs and gene therapy, and highlight some of our research accomplishments in the last decade.
Keywords: Biološka zdravila; biološke učinkovine; Farmacevtska biologija; Farmakognozija; inovativno zdravljenje; Zdravljenje